UPAYA MASKAPAI GARUDA INDONESIA BERGABUNG DENGAN ALIANSI GLOBAL SKYTEAM DALAM PEMASARAN BRAND - Deo Rizky Sebayang; Ahmad Jamaan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research purpose is to explains about the efforts of Garuda Indonesia airlines to join the global airline alliance SkyTeam in brand marketing. It observe the effort attempted by Garuda Indonesia airlines to join the global airline alliance SkyTeam to strengthen the reputation of Garuda Indonesia as a world class airlines. It is a qualitative method by exerting the paradigm from service liberal and full service concept from garuda Indonesia enterprise. the theory applied in this research are Contingency theory by Tannenbaum and Schmidt. This study focused on strategy used by Garuda Indonesia to join the global airline alliance SkyTeam in brand marketing by examining the economic side, which is the modernization of air transport models. The search for the revitalization unit to reach 154 units in 2015 to compete with other companies. With the new units, the increase in passengers will increase as well not only domestic but also international. It also ensures a more comfortable and provide cost than before. Garuda Indonesia’s program named Quantum Leap, covering the aspects of safety, systems, facilities and human resources also made an effort to join the global airline alliance SkyTeam. Introducing the program of Garuda Indonesia Experience has a purpose to distinguish the full service carrier of Garuda Indonesia with others. By giving cultural perception of Indonesia for domestic and international, introducing the culture itself to the tourist who come to indonesia and also having good facilities in every unit, it will be reinforce the brand of enterprise.Key Word: efforts, garuda Indonesia, global airline alliance, skyteam